Enhanced cobalt-based catalysts through alloying ruthenium to cobalt lattice matrix as an efficient catalyst for overall water splitting. (10th December 2019) - Gao, Caiyan; Wang, Haiyang; Li, Shuaihui; Liu, Bo; Yang, Jinghe; Gao, Jie; Peng, Zhikun; Zhang, Zhihong; Liu, Zhongyi
Abstract: The development of high activity, long stability, and cost-efficient catalyst for overall water splitting is paramount for the scalable production of hydrogen. Herein, we report low ruthenium content ruthenium cobalt nanoalloys encapsulated in nitrogen-doped carbon layers synthesized via incipient-wetness impregnation-pyrolysis method (denoted as RuCo@NC-temp.). A series of characterizations reveal that trace amounts of ruthenium inserts into the cobalt lattice matrix that can form RuCo alloys. The optimized catalyst (RuCo@NC-750, 1.56 wt% Ru) shows superior catalytic performance for hydrogen evolution reaction in alkaline, acidic, and neutral media, as well as oxygen evolution reaction in alkaline media. The catalytic reaction displays an overpotential of 25 mV (1.0 M KOH), 29 mV (0.5 M H2 SO4 ), and 163 mV (1.0 M PBS) for hydrogen evolution reaction and 308 mV (1.0 M KOH) for oxygen evolution reaction at a current density of 10 mA cm −2 . RuCo@NC-750 needs only 1.54 V to achieve a current density of 10 mA cm −2 when it serves as both the anode and cathode material in a two-electrode electrolyzer. The excellent electrocatalytic performance can be attributed to the doping of ruthenium into the cobalt lattice matrix, which effectively enhance the electron transfer from the metal core to the carbon surface, and is beneficial for regulating the electronic structure of the carbon surface and strengthening the carbon-hydrogen bond and surface defects. Graphical abstract: In this work, we reported a controllable and convenient method for the preparation of RuCo alloys by introducing trace amounts of Ru into the cobalt lattice matrix, which are encapsulated by nitrogen doped carbon layers. The incipient-wetness impregnation-pyrolysis method effectively improves the utilization of precious metals and simplify the operation. The target electrocatalyst (RuCo@NC-750) shows high TOF values of 3.15, 2.94, and 0.44 s −1 at η100 for HER and 0.35 s −1 at η300 for OER. Image 1 Highlights: Improving the non-noble metal based catalysts by modifying its lattice matrix with a trace amount of precious metal. The impregnation-pyrolysis method improves the utilization of precious metals. Highly activity and stability bifunctional catalysts for overall water splitting.